A new operation strategy based on unequal ad-/desorption time for a two-bed adsorption refrigeration system. (15th November 2022) - Pan, Q.W.; Xu, J.; Wang, R.Z.; Ge, T.S.
Abstract: Adsorption refrigeration is one of green cooling technologies while it uses natural refrigerant and can be driven by renewable energy or waste heat. However, its wide application is restricted by the disadvantages of low efficiency and large size. To improve the performance, this paper proposes a new operation strategy based on unequal ad-/desorption time for a two-bed adsorption refrigeration system. The detailed configuration and working processes of this proposed system are described. Then, a mathematical model is developed to investigate the performance of proposed operation strategy. Through the analysis on the simulation results, the effects of desorption and preheating/-cooling time on thermal/electrical coefficient of performance (TCOP/ECOP) and specific cooling power (SCP) are revealed. TCOP and SCP intersection point is located at around 570 s desorption time. SCP reaches the peak value of 203 W kg −1 at 20 s preheating/-cooling time. The system adopting the new operation strategy can achieve a TCOP of 0.610, an ECOP of 29.23 and a SCP of 203 W kg −1 . When compared to the traditional operation strategy, the COP is improved by 53% but the ECOP and SCP is slightly promoted. This work can provide a feasible guideline for applying new operation strategy on practical systems. Highlights: A new operation strategy based on unequal ad-/desorption time is proposed. The adsorption time of each beds is twice of desorption time. Two beds are unsymmetrical in the aspects of temperature and water uptake. System with new operation strategy achieve a COP of 0.610 and a SCP of 203 W kg −1 . COP is improved by 53% as new operation strategy is used.